Acute and subacute toxicity studies of chitosan reduced gold nanoparticles: a novel carrier for therapeutic agents - Pokharkar, Varsha; Dhar, Sheetal; Bhumkar, Devika; Mali, Vishal; Bodhankar, Subhash L.; Bhagavatula L. V. Prasad (Journal of Biomedical Nanotechnology, 2009)
The objective of the present study was to evaluate the oral toxicity of chitosan reduced gold nanoparticles so as to demonstrate its applicability for drug delivery application. Acute oral toxicity studies in female rats documented no deaths or treatment related complications. The LD(50) value of gold nanoparticles was found to be greater than 2000 mg/kg. In case of sub-acute oral toxicity studies, gold nanoparticles were administered orally to male and female rats for a period of 28-days. At the end of study blood samples were collected for haematology and biochemical analysis. For histopathological analysis, organs of animals were weighed and processed for examination. All animals survived the duration of the study, with no significant changes in clinical signs, body weight, food consumption, hematological parameters, organ weights and histopathological findings. These studies establish that chitosan reduced gold nanoparticles produced no treatment related toxicity in rats following oral administration, thus can be exploited for potential therapeutic applications.
Keywords: Acute Toxicity; Chitosan; gold nanoparticles; Sub-Acute Toxicity; Wistar Rats

Biocompatible gellan gum-reduced gold nanoparticles: cellular uptake and subacute oral toxicity studies - Dhar, Sheetal; Mali, Vishal; Bodhankar, Subhash L.; Shiras, Anjali; Bhagavatula L. V. Prasad; Pokharkar, Varsha (Journal of Applied Toxicology, 2011)
Currently gold nanoparticles are being explored for drug delivery and other biomedical applications; therefore it is necessary to study the fate of such nanoparticles inside the body. The objective of the present study was to investigate the cellular uptake and toxicity of the gold nanoparticles synthesized using a microbial polysaccharide, gellan gum, as a capping and reducing agent. The cellular uptake of gold nanoparticles was studied on mouse embryonic fibroblast cells, NIH3T3 and human glioma cell line, LN-229. The cellular uptake study indicated that the gellan gum-reduced gold nanoparticles were located in cancer cells (LN-229) while no uptake was observed in normal mouse embryonic fibroblast cells (NIH3T3). The toxicity of the gold nanoparticles was evaluated by carrying out subacute 28 day oral toxicity studies in rats. Subacute administration of gum-reduced gold nanoparticles to the rats did not show any hematological or biochemical abnormalities. The weight and normal architecture of various organs did not change compared with control. The current findings, while establishing the specific uptake of nanoparticles into cancerous cells, also demonstrates that the gellan gum-reduced gold nanoparticles are devoid of toxicity in animals following oral administration. Copyright (c) 2010 John Wiley & Sons, Ltd.
Keywords: cell lines; cellular uptake; Gellan gum; gold nanoparticles; subacute toxicity